Model źródeł kosztów „ukrytej fabryki”: perspektywa kadry kierowniczej Część 1. Podstawy modelu: The Model of „Hidden Factory” Costs’ Sources: The Executives’ Perspective. Part 1. The Basics of The Model - Woźniak, Jacek (Management and Administration Journal, 2021)
In practice, every economic activity is laden with a specific cost category. A significant portion of the results of activities undertaken in an organization is easy to identify, and thus is recorded in an organizational system. However, there can also be indicated the results that are difficult to observe directly in an organization. This situation is dangerous for a system, especially when these results have a negative impact on the state of the system (or its specific subsystems), and when they are not recorded. Thus, it is not possible to eliminate them, or to reduce their negative impact on the state of an organization. This is the phenomenon of the hidden costs, which mainly appear in the area of the manufacturing system. However, it should be noted that the costs of the "hidden factory" (HFC) can also be derived from the executives’ activities – what should not be downplayed in terms of setting up an economic activity. The analysis of the sources of the hidden costs requires both process and system approaches. Therefore, there can be identified the following potential determinants of the HFC phenomenon by the side of the executives, i.e. the functions of: executive stations, quality of processes from executives’ point of view, and processes of knowledge management and improvement, as well the submodels of: process nature of the HFC phenomenon, executives’ competences, and information system for the level of management processes.